WIDE BOOST RATIO IN QUASI-IMPEDANCE NETWORK CONVERTER USING SWITCH VOLTAGE SPIKE REDUCTION TECHNIQUE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
High-step-up converters are widely used for solar power applications. In that, impedance source converters are mostly preferred as it has a special feature of high gain at a low-duty cycle. However, the traditional impedance source converters have limited duty ratio operation and high stress across the network and the device. Thus, this paper presents a new type of quasi-impedance source dc-dc converter. The proposed converter has a large boost ratio operation using a switch voltage spike reduction technique. This reduces the stress across the network as well as across the device. The performance of the proposed topology has been investigated against several types of quasi-impedance source converters such as a switched capacitor, inductance alone, embedded, and conventional quasi-impedance source converter. The results clearly show that the projected modified quasi-impedance source converter topology has a high efficiency of 92 %. The modes of operation and comparative study of the modified topology are presented. A 60 W laboratory setup is developed to investigate the performance of the suggested converter, and the simulation results are verified experimentally.
Keywords: Modified quasi impedance source converter; Conventional quasi impedance source converter; Switched capacitor; Inductance alone; Embedded; Voltage gain.